Alunos de cursos de cuidadores de idosos e seus relatos de perspectivas de cuidado - Veiga, Katiana Spinelli da (2017)
Introduction: With the increase in the number of elderly people, evidence is an increase in the number of professionals dedicated to caring for these people, the so-called elderly caregivers. Objective: To study the main reasons and care perspectives of students seeking caregiver courses for the elderly. Methodology: A quantitative, cross - sectional and descriptive study was conducted with 109 students from caregivers courses for the elderly of educational institutions in Porto Alegre - RS. These students answered a questionnaire with sociodemographic and economic variables. The perspective of caring for the elderly was evaluated through the adaptation of the Instrument for the Evaluation of the Elderly Family Caregiver. Results: The results showed that the majority of the interviewees for this study are female, married, aged 40 to 60 years, studied until the end of high school and are currently unemployed. The reasons described for entering the course are the search for new occupations, financial return, new knowledge, respect for the elderly, for the desire to do more for the human being, for will, love and care for the elderly. Final Considerations: Students enrolled in caregiver courses for the elderly are willing to perform the functions assigned to them regarding primary care with the elderly as well as moments of leisure. But activities such as cleaning and housekeeping, washing and ironing, and small repairs at home are no longer activities recommended to the caregiver, being cared for by another person indicated by the family.